Dakwah Literasi Ustadz Giovani Van Rega: Analisis Imbauan Pesan Dakwah - Fatoni, Uwes; Tedi, Enjang (Jurnal Komunikasi Islam, 2017)
This article aims to find out how communication (proselytizing) message appeals in the literacy proselytizing of Ustadz Giovani Van Rega. Using a descriptive qualitative method, this study has revealed that the message appeals used by Ustadz Rega are rational message appeals, appeals of fear, appeal for rewards, and motivational appeals. Ustadz Rega is considered using a rational appeal because he refers to the Qur'an and hadith. While the appeal of fear clearly understood from his statement that Indonesian Muslim youths Islam will suffer from weak faith, physical, science, and weak creativity if they are illiterate. The proposition of the appeal of reward is the more a Muslim well literate, the more honorable he is. Whilts the motivational appeal refers to his that the dakwah of literacy is a necessity in order to be able to conquer the world.